Streptomyces coffeae sp. nov., an endophytic actinomycete isolated from the root of Coffea arabica (L.) - Achararak Nammali; Chakapong Intaraudom; Pattama Pittayakhajonwut; Chanwit Suriyachadkun; Sarin Tadtong; Phatraya Srabua; Chitti Thawai (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2021)
).
Keywords: Genomics and Phylogenetic Studies; Plant Disease Resistance and Genetics; Microbial Natural Products and Biosynthesis